Characteristics, Microbiological, and Management Outcomes of Acute Cholangitis Patients in Hospital Settings - Satriya Kelana (LifeSciFi, 2026)
Acute cholangitis is a serious condition caused by cholestasis and biliary tract infection due to biliary stenosis, which carries a high risk of morbidity and mortality if not treated promptly. This study aimed to describe the characteristics of patients with acute cholangitis during the period January 2020–June 2021. The study used a descriptive observational approach with a cross-sectional design, utilizing secondary data obtained from patients’ medical records. A total of 71 patients were identified, consisting of 7 patients with mild acute cholangitis, 40 patients with moderate severity, and 24 patients with severe conditions. The most commonly isolated bacteria were Staphylococcus haemolyticus (17%), Escherichia coli (16%), and Staphylococcus hominis (15%). Antibiotic sensitivity testing showed that vancomycin and linezolid were the most effective antibiotics (12% each), followed by chloramphenicol (11%). The most frequently performed procedures were open cholecystectomy (44%) and Percutaneous Transhepatic Biliary Drainage (PTBD) (29%). In conclusion, acute cholangitis requires prompt and comprehensive management, including fluid resuscitation, targeted antibiotic therapy based on culture results, and appropriate surgical intervention to reduce complications and improve patient outcomes.